The Effect of Discovery Learning Model Assisted by LKPD on Biology Learning Competencies of Students - Mayarni, Khairina (Pascasarjana, Mataram University, 2025)
This study aims to determine the influence of the discovery learning model assisted by lkpd on students' biology learning competencies. This research is a quasi-experimental research, with a Randomized Control-Group Posttest Only Design, the population of this experiment is students of class X SMAN 1 Batang Anai Padang Pariaman in the 2003/2004 academic year, while the sample of this research is students of class X1 as the control class, and X8 as the experimental class which is given the Discovery Learning model treatment assisted by Student Worksheets (LKPD). Sampling was carried out using the Purposive Sampling technique. The instruments used in this study were knowledge test questions, attitude and skill observation sheets. with Data analysis of normal and homogeneous distribution tests, namely Kolmogorov Smirnov and Levenne, while for the hypothesis test of the knowledge domain using the unpaired t-test, while for the attitude and skill domains using the Mann Whitney test. The results of the study and observations showed that the biology learning competence of students in the experimental class in terms of knowledge domain was in the sufficient category, attitude domain and skills domain were in the sufficient category compared to the control class with a sig. <0.05. It can be concluded that there is a positive influence of Discovery Learning Assisted by LKPD on the Biology Learning Competence of Class X SMAN 1 Batang Anai Padang Pariaman